(untitled) (Scientific Journal of Research Studies in Future Psychology, 2024)
The main purpose of this study was to investigate the personality profile and dimensions of personality pathology in mothers with children with problems. The present research method is descriptive survey type. It is descriptive due to the lack of researcher intervention in the research results. The population of the present study is all mothers who have children (ranging in age from 5 to 10 years) and have referred to medical centers and clinics, have a psychological record and their clinical signs have been approved by the center psychologist and psychometer. It should be noted that since access to all members of society is possible and a list of them can be prepared, therefore, the present research community falls into the realm of limited communities. In order to determine the sample size and sampling method, New Idea Counseling Center was selected as the sampling unit using the available sampling method and all mothers who have referred to this center since September 2015 were considered as the statistical population. Which is about 130 people. Therefore, no sampling was performed and the level of anxiety in their children was determined using the census method. Personality Pathology Questionnaire (DAPP-BQ) 18 basic dimensions of personality disorders identified through clinical diagnosis and psychometric procedures were evaluated. Were identified through an extensive review of the clinical literature, then used by a team of physicians to determine the most important features for each personality disorder in the DSM-III, after which the identified traits were reduced to 18 essential dimensions. Using a series of multivariate analyzes, the tool evaluates the components of personality disorder that are closely related to the clinical assessment and treatment plan. Medium and mean), distribution indices (standard error, quantitative coefficient and elongation coefficient) and dispersion indices (standard deviation, variance and amplitude of changes), using one-group T statistical model to examine the current situation and compare the average Based on the findings of the present study, "behavioral failure" in mothers Has children with problems, moderate (norm of society). This scale includes emotional failure, thinking failure, behavioral failure.